Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/mame.201800377
|View full text |Cite
|
Sign up to set email alerts
|

High Electromagnetic Interference Shielding Effectiveness of Carbon Nanotube–Cellulose Composite Films with Layered Structures

Abstract: Flexible and electrically conductive carbon nanotube (CNT)–cellulose composite films are fabricated by a green route based on sodium hydroxide/urea aqueous solution. Both single‐walled carbon nanotubes (SWCNTs) and multi‐walled carbon nanotubes (MWCNTs) are investigated as conductive fillers. The microstructure and physical properties of the films are characterized extensively. It is observed that CNTs form layered conductive networks in the cellulose matrices during the drying process. The electromagnetic int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…The preparation and investigation of polymer composite shields by the application of ferrites and carbon-based fillers into various polymer matrices has been the interest of many experimental studies [18][19][20][21][22][23][24][25]. The results have demonstrated that composites filled with those fillers can effectively shield EMI.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation and investigation of polymer composite shields by the application of ferrites and carbon-based fillers into various polymer matrices has been the interest of many experimental studies [18][19][20][21][22][23][24][25]. The results have demonstrated that composites filled with those fillers can effectively shield EMI.…”
Section: Introductionmentioning
confidence: 99%
“…The high aspect ratio, high electrical conductivity, and excellent mechanical properties of CNTs make them the perfect choice for fabricating conductive composites for EMI shielding [65]. In addition, the few defects of SWCNTs lead to higher conductivity compared to MWCNTs [47]. The large aspect ratio of CNTs facilitates them to form a conductive network in a polymer matrix.…”
Section: D Nanomaterialsmentioning
confidence: 99%
“…It is worth noting that although EMI SE increased significantly after annealing, the long-SWCNTs composites without annealing performed much better, which verified that the EMI SE is more closely related to the aspect ratio other than wall integrity. 1D carbonaceous materials CNT/cellulose Film Dielectric loss, multiple reflection [47] Cds-CNT Core-shell nanowire Dielectric loss, interfacial polarization [48] ZnO@MWCNT Hybrid…”
Section: D Nanomaterialsmentioning
confidence: 99%
“…Among these carbon aerogels, cellulose‐based porous carbon aerogel with environmentally friendly and low‐cost properties have aroused widespread research interest 35–40 . Cellulose possesses biodegradability, non‐toxicity, renewable and rich in carbon, so it is an ideal raw material for preparing carbon materials 41–44 . Due to 3D network structure, high porosity, and large specific surface area, cellulose carbon aerogel makes up for the defects of Na 2 Ti 3 O 7 nanomaterials that are difficult to recycle, easy to damage and agglomerate.…”
Section: Introductionmentioning
confidence: 99%